Geochemistry, geochronology, and tectonic setting of the Cretaceous volcanic rocks in east Mongolia - Bars, Amarjargal; Togtokh, Khasmaral; Miao, Laicheng; Zhang, Fochin; Baatar, Munkhtsengel; Anand, Chimedtseren (Geological Issues, 2023)
Late Mesozoic volcanic rocks in East Mongolia exhibit high-K calc-alkaline and shoshonitic series and display features of bimodal-like volcanic with a mafic and felsic members. The mafic member is composed mainly of trachybasalt and basaltic trachyandesite, with a minor amount of trachyandesite. The mafic rocks have elevated incompatible trace element concentrations and significantly negative Nb-Ta and Ti anomalies, features of typical subduction-related magmas, distinguished from OIBs. The mafic magmas have undergone fractional crystallization dominated by pyroxene and/or olivine and crustal contamination. The mafic magma was derived from low-degree partial melting of an enriched lithospheric mantle source that might have been metasomatized by subduction-derived fluids. The felsic member consists of trachydacite and rhyolite. The geochemical data indicate they produced from partial melting of a crustal source that is dominated by juvenile mafic rocks. Our new K-Ar dating and previous age data demonstrated that the late Mesozoic volcanism in East Mongolia took place during Late Jurassic-Early Cretaceous at between 156-99 Ma. The model of the arc‒back-arc extension possibly induced by slab roll-back of the westward (paleo) Pacific-subduction can explain the geodynamic setting and the eastward young trend of the late Mesozoic volcanism in East Mongolia and its adjacent NE China.